Al-Amr ‘inda ‘ulama al-Balagah wa ‘Ulama Usul al-Fiqh ‘ala Mustawa al-Ta’rif wa al-Siyag wa al-Ma’ani al-Siyaqiyah - Yanti Kusnawati; Ihsan Sa'dudin (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
Balagah and usul fiqh are two different sciences. Balagah science is the science that reveals an aesthetic meaning which is clearly used in a real expression, Takes an effect in our soul, and maintains the relevance of each sentence with where the phrase is being pronounced. Moreover, please pay attention to the coherence with the people we talk to. Whereas Usul Fiqih is the Islamic legal sciences (Islamic jurisprudence) studied theories, norms, and sources. Both sciences are studied in relation to fi'il amr, In Balagah, Fi'il amr is the one method from Insya Zalbi decree while in Usul Fiqih, fiil amr is the one of Usul Fiqih Norm which is due to that the law and syari’as can increase. And the result of this research is, in Balagah and Usul Fiqih have the same interpretation about fi’il amar that requires to have to do from a higher authority to underling, and that have 4 sigah. And the difference between the two science is from the meaning of fi’il amar, in Balagah have a special meaning from fi’il amar that there is no meaning in Usul Fiqih that the means is lasting. Permission and exemplary. So in Usul Fiqih have a special meaning from fi’il amr there is no meaning in Balagah that means is: obligatory, mouming, admonition, discussion, degradation, patience, dissuasion, delegation.